The Introductions in Medical Research Articles - Azirah Hashim (Journal of Modern Languages)
This paper attempts to look at the ‘moves’ and language of introductions, and to present a model for introductions in medical articles. It also suggests ways of helping students to cope with the writing of introductions. The corpus for this paper consists of twenty articles selected at random from seven different medical journals published from 1990 to 1993. The findings of the study reveal that academic writing consists of moves which do not conform to paragraph divisions. Students who are learning how to write an academic text will have to be made aware that there are moves containing information in all the sections including the introduction.